Timing of rotator cuff activation during shoulder external rotation in throwers with and without symptoms of pain - Hess, S. A; Richardson, C. A.; Darnell, R.; Friis, P.; Lisle, D.; Myers, P. (Journal of Orthopaedic & Sports Physical Therapy, 2005)
Study Design: Fine-wire EMG rotator cuff onset time analysis in 2 matched groups of throwers with and without pain. Objective: To identify if there is a difference in the activation patterns of the rotator cuff muscles during a rapid shoulder external rotation task between throwers with and without pain. Background: The coordinated action of the rotator cuff is recognized as essential for glenohumeral joint control in the throwing athlete. Identification of abnormalities occurring in muscle activation patterns for injured athletes is relevant when prescribing rehabilitative exercises. Methods and Measures: Twelve throwers with shoulder pain were compared to a matched group of 11 asymptomatic throwers. Participants were matched for age, height, body mass, and habitual activity. Fine-wire EMG electrodes were inserted into the subscapularis, supraspinatus, and infraspinatus. EMG activity was measured during a reaction time task of rapid shoulder external rotation in a seated position. The timing of onset of EMG activity was analyzed in relation to visualization of a light (reaction time) and to the onset of infraspinatus activity (relative latency). Results: In the group with shoulder pain, the onset of subscapularis activity was found to be significantly delayed (reaction time, P = .0018; relative latency, P = .0005) from the onset of infraspinatus activity when compared to the control group. Conclusions: The presence of shoulder pain in these athletes was associated with a difference in the onset of subscapularis EMG activity during a rapid shoulder external rotation movement. This was an initial step in the understanding of the joint protection mechanisms of the glenohumeral joint and the problems that occur in throwers. This information may assist in providing future guidelines for more effective rehabilitation and prevention strategies for this condition.